On the time transformation of mixed integer optimal control problems using a consistent fixed integer control function - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (Mathematical Programming)

A comparison of two predictive approaches to control the longitudinal dynamics of electric vehicles - Eckstein, Julian; Peitz, Sebastian; Schäfer, Kai; Friedel, Patrick; Köhler, Ulrich; Hessel von Molo, Mirko; Ober-Blöbaum, Sina; Dellnitz, Michael (Procedia Technology, 3rd International Conference on System-Integrated Intelligence: New Challenges for Product and Production Engineering)
In this contribution we compare two different approaches to the implementation of a Model Predictive Controller in an electric vehicle with respect to the quality of the solution and real-time applicability. The goal is to develop an intelligent cruise control in order to extend the vehicle range, i.e. to minimize energy consumption, by computing the optimal torque profile for a given track. On the one hand, a path-based linear model with strong simplifications regarding the vehicle dynamics is used. On the other hand, a nonlinear model is employed in which the dynamics of the mechanical and electrical subsystem are modeled.

Variational integrators of mixed order for dynamical systems with multiple time scales and split potentials - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (ECCOMAS Congress 2016 - Proceedings of the 7th European Congress on Computational Methods in Applied Sciences and Engineering)

Constrained Galerkin variational integrators and modified constrained symplectic Runge-Kutta methods - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (International Conference of Numerical Analysis and Applied Mathematics (ICNAAM))

Reduced order model based multiobjective optimal control of fluids - Peitz, Sebastian; Ober-Blöbaum, Sina; Dellnitz, M. (Proceedings of International Congress of Theoretical and Applied Mechanics)

Optimal control of switching times in switched linear systems - Stellato, B.; Ober-Blöbaum, Sina; Goulart, P.J. (2016 IEEE 55th Conference on Decision and Control (CDC))

Variational integrators of higher order for constrained dynamical systems - Wenger, T.; Ober-Blöbaum, Sina; Leyendecker, S. (PAMM)

C1-continuous time integration based on cubic Hermite interpolation - Mergel, J.C.; Sauer, R.A.; Ober-Blöbaum, Sina (PAMM)

Time transformed mixed integer optimal control problems with impacts - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (PAMM)

Higher order variational integrators in optimal control theory - Ober-Blöbaum, Sina (PAMM)

Variational multirate integration in multi-body dynamics - Gail, T.; Leyendecker, S.; Ober-Blöbaum, S. (PAMM)

On higher order variational integrators and their relation to Runge-Kutta methods - Ober-Blöbaum, Sina (International Conference of Numerical Analysis and Applied Mathematics (ICNAAM))

Secure store and forward proxy for dynamic IoT applications over M2M networks - Díaz Sánchez, Daniel; Simon Sherratt, R.; Almenárez, Florina; Arias Cabarcos, Patricia; Marín, Andrés (IEEE Trans. Consumer Electron.)

Comparing Password Management Software: Toward Usable and Secure Enterprise Authentication - Arias Cabarcos, Patricia; Marín López, Andrés; Palacios, Diego; Almenárez, Florina; Díaz Sánchez, Daniel (IT Prof.)

Distributed access control and privacy for the internet of me - Díaz Sánchez, Daniel; Simon Sherratt, R.; Almenárez, Florina; Arias Cabarcos, Patricia; Marín López, Andrés (IEEE International Conference on Consumer Electronics, ICCE 2016, Las Vegas, NV, USA, January 7-11, 2016)

Proxy re-encryption schemes for IoT and crowd sensing - Díaz Sánchez, Daniel; Simon Sherratt, R.; Arias Cabarcos, Patricia; Almenárez, Florina; Marín López, Andrés (IEEE International Conference on Consumer Electronics, ICCE 2016, Las Vegas, NV, USA, January 7-11, 2016)

A distributed transcoding and content protection system - Enabling pay per quality using the cloud - Díaz Sánchez, Daniel; Sánchez Guerrero, Rosa; Arias Cabarcos, Patricia; Almenárez, Florina; Marín, Andrés (Telecommun. Syst.)

Wi-Fi Direct: Lessons learned - Marín López, Andrés; Almenárez-Mendoza, Florina; Arias Cabarcos, Patricia; Díaz Sánchez, Daniel (2016 Mediterranean Ad Hoc Networking Workshop, Med-Hoc-Net 2016, Vilanova i la Geltru, Spain, June 20-22, 2016)

Analysis of Secure TCP/IP Profile in 61850 Based Substation Automation System for Smart Grids - Abou Khaled, Omar; Marín, Andrés; Almenárez, Florina; Arias Cabarcos, Patricia; Díaz Sánchez, Daniel (Int. J. Distributed Sens. Networks)

Review: Schwarz, Steffen L.: Despoten – Barbaren – Wirtschaftspartner. Die Allgemeine Zeitung und der Diskurs über das Osmanische Reich 1821-1840, Köln Weimar Wien 2016 - Schönhärl, Korinna (H-Soz Kult)